Pengaruh Penambahan Senyawa Thiophenone terhadap Kelulushidupan dan Pertumbuhan Larva udang galah yang Diujitantang dengan Bakteri Vibrio harveyi - Pratama, Maulana Ilham; Julyantoro, Pande Gde Sasmita; Negara, I Ketut Wija (Current Trends in Aquatic Science, 2023)
Giant prawns are one of the freshwater aquaculture commodities with high economic value. The high demand for giant prawns is constrained by the low quality of larvae, which affect the prawn growth to reach consumption sizes. Conventional efforts have been made to treat the bacterial diseases in the prawn cultivation using antibiotics. However, it has risk of causing pathogenic bacteria to become resistant to antibiotics. Such issue can be overcome by using inhibiting quorum sensing from pathogenic bacteria, especially thiophenone compounds. This study aimed to determine the effect of adding thiophenone compounds on the survival and growth of giant prawn larvae from Center for Giant Prawns (BBUG) Klungkung, Bali tested with V ibrio harveyi . A completely randomized design of 4 treatments (A: control, B: Larvae and Vibrio harveyi ( 10 5 CFU/ml), C: Larvae and thiophenone (10µM), D: Larvae, thiophenone (10µM) and Vibrio harveyi (10 5 CFU/ml)) and 3 repetitions was done in laboratory. A total of 12 experimental units containing 20 larvae with 0.2liter seawater media at 28?C. The results showed that the survival rate of giant prawn larvae was significantly higher when the larvae challenged with V ibrio harveyi compared to un challenged larvae. Furthermore, there was no difference in prawn larvae growth between the treatments indicated by similar value of Larvae Stage Index (LSI). This study has demonstrated the benefit of employing thiophenone compounds to improve the quality of giant prawn larvae. Further study in challenging the thiophenone compounds with other bacteria that might threat the giant prawn growth is still needed.